Gypenosides Attenuate Pulmonary Fibrosis by Inhibiting the AKT/mTOR/c-Myc Pathway - Liu, Suqing; Yang, Qingqing; Dong, Binbin; Qi, Chunhui; Yang, Tao; Li, Ming; He, Shan; Liu, Baojun; Wu, Jinfeng (Frontiers in Pharmacology, 2022)
Gypenosides (Gyps), the major active constituents isolated from gynostemma pentaphyllum, possess anti-inflammatory and antioxidant activities. Previous studies have demonstrated that Gyps displayed potent ameliorative effects on liver fibrosis and renal fibrosis. In this study, we found that Gyps significantly reduced the mortality of bleomycin-induced pulmonary fibrosis mice (40% mortality rate of mice in the model group versus 0% in the treatment group). Masson staining showed that Gyps could reduce the content of collagen in lung tissue of pulmonary fibrosis mice Masson staining and immunohistochemistry demonstrated that the expression of collagen gene α-SMA and fibrosis gene Col1 markedly decreased after Gyps treatment. The active mitosis of fibroblasts is one of the key processes in the pathogenesis of fibrotic diseases. RNA-seq showed that Gyps significantly inhibited mitosis and induced G2/M phase cell cycle arrest. mTOR/c-Myc axis plays an important role in the pathological process of pulmonary fibrosis. RNA-seq also demonstrated that Gyps inhibited the mTOR and c-Myc signaling in pulmonary fibrosis mice, which was further validated by western blot and immunohistochemistry. AKT functions as an upstream molecule that regulates mTOR. Our western blot data showed that Gyps could suppress the activation of AKT. In conclusion, Gyps exerted anti-pulmonary fibrosis activity by inhibiting AKT/mTOR/c-Myc pathway.